Interpersonal patient-therapeutic team communication during COVID-19 pandemic – selected problems - Araminowicz-Kierklo, Elzbieta (Journal of Education, Health and Sport, 2024)
Introduction. Interpersonal communication is an important element of effective cooperation between a patient and therapeutic team. Patients ill with COVID-19 during the pandemic especially needed a direct contact with medical staff. Introduction of modern technologies during COVID-19 pandemic enabled interpersonal communication between a patient and therapeutic team. Objective: The aim of the study was presentation of the selected elements of interpersonal communication in the work of a nurse between a patient and therapeutic team during COVID-19 pandemic. Material and Methods. The problem of interpersonal communication between a patient and therapeutic team during COVID-19 pandemic was analyzed based on the results of scientific studies and perceptual experiences. Results. COVID-19 pandemic was a new challenge for therapeutic teams in patient care in treatment facilities, to provide an effective interpersonal communication. In order to improve the quality of interpersonal communication alternative forms of communication with patients were applied. During the COVID-19 pandemic social media played a special role in primary health care. Efforts undertaken by medical staff also had to be focused on safe environment of care and safe work conditions. Conclusions. Interpersonal communication between a patient and therapeutic team should be improved during the pandemic considering the provision of a high quality services for patients in a state of threat to health and life. An improvement of the effectiveness of interpersonal communication is conditioned by the implementation of alternative forms of communication with a patient, efficient functioning of social media, provision of safe environment of patient care and safe work conditions for medical staff.